Investigating Applications of Run Length Encoding in Data Compression & Source Coding - Rongali, Aruna Sri; Dhabliya, Dharmesh; Pandey, Ishaan; Sachdeva, Ankit; Praveena, Hirald Dwaraka; Aich, Shibani C (International Conference on Computing, Communication, and Networking Technologies (Online), 2024)
Run period Encoding (RLE) is a powerful and efficient approach for fact compression and supply coding. It is generally applied to the lossless compression of grayscale or bi-tonal (black-and-white) photos and digital pix. Significantly, RLE decreases the statistics required to save and transmit virtual facts. That is completed by making the information greater compact and casting off redundancy. Typically, RLE counts the number of consecutive occurrences of a given image or sign and then encodes those occurrences into an unmarried cost. By encoding multiple repetitions of a symbol in this manner, RLE can reduce the entire quantity of statistics wanted for garage or transmission. The RLE set of rules works by looking for long strings of characters that may be compressed into fewer characters. Exploring the potential packages of RLE in supply coding and records compression is an ongoing study subject matter within the area.